PENGARUH QUALITY OF WORK LIFE DAN PEMBERDAYAAN TERHADAP MOTIVASI DAN KEPUASAN ANGGOTA KELOMPOK KAWASAN RUMAH PANGAN LESTARI (KRPL) KOTA PASURUAN - Suryanto Widodo; Arief Purwanto (BADAN PENERBITAN UNIVERSITAS WIDYAGAMA, 2020)
ABSTRACTThe Sustainable Food House Area (in Indonesian it is called KRPL) is one of the programs of the central government, as an effort to use yard land. The KRPL program has been implemented in Pasuruan City since 2012. To date, 64 KRPL groups have been formed. The purpose of this study was to analyze as well as test the hypothesis of the effect of quality of work life and empowerment on the motivation and satisfaction of members of the KRPL group in Pasuruan City. The population in this study were all members of the KRPL group in Pasuruan City of 1,030 people. The sampling method used the Slovin formula, resulting in 92 respondents. The research instrument used a questionnaire with a Likert scale of 1-5. The method of analysis in this research is using PLS-SEM which is based on variance. The software used in this research is SmartPLS version 3.0. The results of the study concluded that: (1) Quality of work life can increase the motivation of the KRPL group members; (2) Empowerment is able to increase the motivation of the KRPL group members; (3) Quality of work life is not able to increase job satisfaction of the KRPL group members; (4) Empowerment is not able to increase job satisfaction of the KRPL group members; (5) Motivation is able to increase job satisfaction of the KRPL group members; (6) Quality of work life is able to increase job satisfaction which is mediated by the motivation of the KRPL group members; and (7) Empowerment is able to increase job satisfaction which is mediated by the motivation of the KRPL group members.Keywords: KRPL group, quality of work life, empowerment, motivation, job satisfaction ABSTRAKKawasan Rumah Pangan Lestari (KRPL) merupakan salah satu program dari pemerintah pusat, sebagai upaya pemanfaatan lahan pekarangan. Program KRPL dilaksanakan di Kota Pasuruan sejak tahun 2012. Hingga saat ini, telah terbentuk 64 kelompok KRPL. Tujuan penelitian ini adalah untuk menganalisis sekaligus menguji hipotesis pengaruh quality of work life dan pemberdayaan terhadap motivasi dan kepuasan anggota kelompok KRPL Kota Pasuruan. Populasi dalam penelitian ini adalah seluruh anggota kelompok KRPL Kota Pasuruan sebesar 1.030 orang. Metode pengambilan sampel menggunakan rumus slovin, menghasilkan responden sejumlah 92 orang. Instrumen penelitian menggunakan kuesioner dengan skala likert 1-5. Metode analisis penelitian ini menggunakan PLS-SEM yang berbasis variance. Software yang digunakan dalam penelitian ini adalah SmartPLS versi 3.0. Hasil penelitian menyimpulkan bahwa: (1) Quality of work life mampu meningkatkan motivasi anggota kelompok KRPL; (2) Pemberdayaan mampu meningkatkan motivasi anggota kelompok KRPL; (3) Quality of work life tidak mampu meningkatkan kepuasan kerja anggota kelompok KRPL; (4) Pemberdayaan tidak mampu meningkatkan kepuasan kerja anggota kelompok KRPL; (5) Motivasi mampu meningkatkan kepuasan kerja anggota kelompok KRPL; (6) Quality of work life mampu meningkatkan kepuasan kerja yang dimediasi motivasi anggota kelompok KRPL; dan (7) Pemberdayaan mampu meningkatkan kepuasan kerja yang dimediasi motivasi anggota kelompok KRPL.Kata Kunci: kelompok KRPL, quality of work life, pemberdayaan, motivasi, kepuasan kerja